The Incidental Resolution of Severe Alcohol Use Disorder during Esketamine Treatment of Major Depressive Disorder: A Case Report - Faruqui, Zeeshan; Kim, Christopher (Case Reports in Psychiatry, 2022)
Alcohol use disorder (AUD) is especially prevalent among individuals with major depressive disorder (MDD) and is associated with higher morbidity, mortality, disability, and risk for suicide. Intranasal esketamine has been documented to be a safe and effective option for treatment resistant MDD and received US FDA approval in 2019. However, the availability of esketamine is limited due to requirements for a Risk Evaluation and Mitigation Strategy program for its administration as well as concerns over substance use disorders (SUD) as a potential contraindication or adverse effect. This case presents a 61-year-old female with a history of severe recurrent treatment resistant MDD and severe AUD who has expressed interest in esketamine. To date, she has completed 20 sessions of 56 mg intranasal esketamine twice a week before increasing to 5 weekly sessions and then 14 weekly sessions of 84 mg. Although there was immediate subjective improvement in mood as well as reductions in PHQ-9 and HAM-D scores, the dosage was increased to extend the therapeutic benefit throughout the entire intertreatment interval. She was able to complete these sessions without complication. Incidentally, she also reported decreased desire to use alcohol, decreased impulsivity, and the complete cessation of alcohol use by the second week. While on 56 mg, she had a single relapse of binging which was addressed with motivational therapy and has remained alcohol-free since. This case presents the first documented example of the safe and effective use of intranasal esketamine in patient with treatment resistant MDD in which there was incidental resolution of their comorbid severe AUD. This suggests that esketamine can be used without risk of SUD onset or exacerbation. Thus, esketamine should not be discounted in patients with SUD and continued research is needed to further elucidate its role in treating SUD.